Incomes and Expenses of Farmers’ Intact (Nuclear) Families of Sverdlovsk Region (according to 1960 Budget Surveys) - V. N. Mamyachenkov (Научный диалог)
The article is devoted to the subject insufficiently developed in the national historiography, in particular in regard to its regional dimension. The purpose of the article was a study of incomes and expenses of farmers’ intact (nuclear) families of Sverdlovsk region in 1960. The study is conducted on materials of State archive of Sverdlovsk region and archive of the Territorial body of Federal state statistics service for Sverdlovsk region with the assistance of Internet sources as well as scientific and publicistic literature. The new materials discovered by the author in these archives are introduced into scientific usage. It is noted that nuclear families, as the most typical and widespread, were chosen by statistical bodies for the above-mentioned regular annual surveys of family budgets. It is argued that although family data were the basis (“core”) for statistical surveys, they themselves rarely became the object of research by sociologists and historians. It is stated that there was a rather serious differentiation of cash incomes and expenses of the surveyed full families of collective farmers. It is stated that the characteristic feature of nuclear families was their relatively young age in comparison with other types of families of collective farmers. The significant role of the personal subsidiary farm in the economy of the surveyed families is proved. It is declared that the most part of expenses of incomplete families of collective farmers were expenses on food and industrial goods. It is concluded that even taking into account the significant incomes from personal subsidiary farm, the total income of nuclear families was slightly lower than the income of families of urban workers.